The Effect of Motivation and Competency on Work Productivity of Employee: Case Study at The Population and Civil Registration Office, Sarolangun Regency, Indonesia - Mubarrok, Husni; Rasid, Fahmi; Wahyudi, Heri (Manunggal Halim Jaya, 2025)
The research entitled the influence of motivation and competence on the work productivity of employees at the Population and Civil Registration Service of Sarolangun Regency, Indonesia which analyzes the influence of motivation and competence on the work productivity of employees of the Population and Civil Registration Service of Sarolangun Regency uses descriptive statistical analysis methods and verification analysis in the form of partial least squares (PLS) and SPSS 21. Research results where motivation directly has a significant effect on employee productivity, where the t statistical value (6.080) is greater than the t-estimated (2.006). Then the competency variable directly has a significant effect on employee productivity, where the statistical t-value (2.450) is greater than the t-estimated (2.006). The results of this research have implications for efforts to increase employee work motivation in each work unit so that it will have an impact on increasing employee productivity.